2010
DOI: 10.1186/1471-2377-10-97
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective properties of levosimendan in an in vitro model of traumatic brain injury

Abstract: BackgroundWe investigated the neuroprotective properties of levosimendan, a novel inodilator, in an in vitro model of traumatic brain injury.MethodsOrganotypic hippocampal brain slices from mouse pups were subjected to a focal mechanical trauma. Slices were treated after the injury with three different concentrations of levosimendan (0.001, 0.01 and 0.1 μM) and compared to vehicle-treated slices. After 72 hrs, the trauma was quantified using propidium iodide to mark the injured cells.ResultsA significant dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 11 publications
1
34
0
5
Order By: Relevance
“…The fact that levosimendan improved perfusion via increased CI and vasodilatation could contribute to reduced neuronal injury in the hippocampal formation. In an in vitro model of traumatic brain injury, levosimendan showed direct neuroprotective properties (47). However, findings in dogs indicated that levosimendan does not substantially penetrate the bloodbrain barrier in the healthy brain (48).…”
Section: Discussionmentioning
confidence: 98%
“…The fact that levosimendan improved perfusion via increased CI and vasodilatation could contribute to reduced neuronal injury in the hippocampal formation. In an in vitro model of traumatic brain injury, levosimendan showed direct neuroprotective properties (47). However, findings in dogs indicated that levosimendan does not substantially penetrate the bloodbrain barrier in the healthy brain (48).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, levosimendan has been shown to reduce cell death and inflammatory responses and improve function after transient ischemia of the spinal cord in rabbits [7,8]. While a dose-dependent protective effect in an in vitro model of traumatic brain injury could be demonstrated [9], levosimendan failed to improve brain metabolism or reduce glutamate release, inflammation and dysfunction of autoregulation in the initial phase after experimental global ischemic/hypoxic cerebral injury [10]. Its effect on focal transient ischemia has not been investigated in vivo in the brain as it has been in the heart [11].…”
Section: Introductionmentioning
confidence: 99%
“…A histogram of the red channel was generated for each image, showing the sum of all pixels sharing the same gray scale value from 0 to 255. As previous studies have shown, values below a threshold of 100 are caused by background fluorescence 62122. That is why only the values of pixels above this threshold were summed up to evaluate the extent of cell injury.…”
Section: Methodsmentioning
confidence: 99%